Hypotony after 25-gauge pars plana vitrectomy with suturing all sclerotomies - Shogo Takahashi; Tomoko Ueda-Consolvo; Yuta Takata; Masaaki Ishida; Shuichiro Yanagisawa; Atsushi Hayashi (PLoS ONE, 2026)
Purpose To evaluate the incidence of postoperative hypotony and early complications in 25-gauge vitrectomy by suturing all sclerotomies. Methods We retrospectively reviewed a consecutive series of 458 eyes of 435 patients who underwent 25G pars plana vitrectomy with suturing all sclerotomies. The primary outcome measure was intraocular pressure (IOP) at postoperative day 1. Secondary outcome measures were clinical signs of hypotony and postoperative complications. Hypotony was defined as an IOP < 5 mmHg. Results Postoperative hypotony was found in 22 eyes (4.8%). No eyes suffered IOP of 0 nor 1 mmHg. None of the eyes demonstrated any clinical signs of hypotony including endophthalmitis, hypotony maculopathy nor choroidal detachment. The eyes with sulfur hexafluoride (SF6) gas tamponade had a significantly lower rate of hypotony compared to eyes with no tamponade (1.3% (2 eyes/154 eyes) vs 6.3% (18eyes/284 eyes); p = 0.0118). The incidence of hypotony was 11.1% (5 eyes/45 eyes) in reoperation and 4.1% (17 eyes/413 eyes) in primary operations (p = 0.037). Conclusion Suturing all sclerotomies showed a low incidence of postoperative hypotony. Reoperation increased the risk of hypotony, while SF6 gas tamponade lowered the risk of hypotony.